Are Trainee Language Teachers Autonomous in Developing Their Own Language Skills? - CLAUDIA MOLNAR (Indonesian Research Journal in Education |IRJE|, 2020)
This study presents the findings of a mixed method study exploring how autonomous 33 in- service and 10 trainee EFL teachers were in the amount of exposure to authentic English language they present themselves. This study investigated the extent to which L2 English TTs were autonomous in their exposure to the target language and how they valued such exposure. Ten university teacher trainees took part in the project. The amount of time they exposed themselves to authentic English was measured using an input application developed specifically for this study. The exposure had to be outside of their teaching and learning domain. The research question was: How autonomous are trainee language teachers in developing their own language skills? Data were collected from an in-service teacher questionnaire, a trainee teacher two-month study, and a focus group discussion. The focus group discussion data were analyzed qualitatively while the quantitative data were analyzed using the SPSS software. The main findings of the study showed that the participants did expose themselves to authentic English but were not aware of the learning value of this exposure. Implications and recommendations are also discussed.